Determination of Ubiquinone and Tocopherol in Heart, Liver and Muscle Tissues of Fresh Water Fish. Rohu ( Labeo rohita, Hamil ton) - Pawar, S S; Magar, N G (Fishery Technology, 1965)
[The liver, heart and muscle tissues of rohu, (Labeo rohita, Hamilton) were exami,ned for their ubiquinone (UQ)and tocopherol contents. These three tissues contained respectively J 1.60, 3.94 and 0.19 mg. of ubiquinone and 10.16, 5.32 and 3.58 mg of tocopherol per 100 g. The 4 percent (V;V) of diethyl ether (EE) in light petroleum ether (PE) fractions of all three tissues on paper chromatographic separation gave spots having the same Rp value as standard ubiquinone-50 (UQ 1 0 ). Both the 4 per cent and 6 per cent (V /V) diethyl ether in light petroleum ether fraction of liver, heart and muscle tissues gave a single spot with the sarre Rp value as o::: - tocopherol]